(untitled) - Weil, Ray R. (Harlow, England, 2017)
The Nature and Properties of Soils has been my labor of love for the past 5 years and updates a narrative that has both reflected and helped to shape soil science thinking for more than a century. It has evolved to provide a globally relevant framework for an integrated understanding of the diversity of soils, the soil system and its role in the ecology of planet Earth
Ô nhiễm chất hữu cơ trong đất,Phì nhiêu đất ứng dụng,Phì nhiêu đất B,Thâm cứu phì nhiêu đất,Cố định đạm sinh học
Keywords: Soil science,Khoa học đất